(untitled) (Journal of Applied Business and Economics, 2021)
Given the complexity accountants face in identifying and reporting extraordinary items, the FASB decided to eliminate the reporting requirement in 2015. This decision has merely shifted the burden from the internal accountants to the outside investors. This change adds little value to the financial community and should be reconsidered. A main argument against reinstating the reporting requirement, perhaps, is the tendency of managers to deploy extraordinary items for earnings management purposes. This paper investigates the earnings management issue using a logit regression and a panel regression model. The findings do not point towards earnings management being a motive behind reporting extraordinary items.